Mytilus edulis opiate processes - Zhu, Wei; Cadet, Patrick (Archives of Medical Science, 2009)
Mytilus edulis, a marine bivalve mollusk, exists in many coastal marine environments. It also serves as a common food with a high level of commercialization. Therefore their overall health should be of great concern and relevance to the human population. Studies in the past 30 years have demonstrated considerable conservation in opiate and opioid peptide processes between invertebrate and humans, including the chemical messengers themselves, as well as their respective receptors. These same messengers may serve as an indication of their over all health. Known evolutionary relationships with all animals and the presence of similar or identical processes, specifically in mollusks, make Mytilus edulis an ideal organism for the study of these processes as a model system. In this review, we mainly focus on the discovery of opiate signaling mechanisms in the mollusk Mytilus edulis, since they transcend pain in function.